Erborlzzazioni in Una Lecceta Sulla Scarpata Orientale Delle Murge Tra Fasano E Locorotondo (Giornale botanico italiano, 1952)
Abstract The author describes a portion of Quercus Ilex wood, placed between Fasano and Locorotondo (Bari), at the cross-road to Selva di Fasano, 300 m. about on the sea level. This woodland, partly destroied, situated at the limits with Q. Troiana woodland, is one of the many remains which are present in the marginal zone of Murge. These remains testify that the Q. Ilex wood was probably in the past, more widly extended, in comparison with Q. Troiana wood, preeminently present today in the low Murgia. Its flora is mostly characteristic of the «Q. Ilex Gürtel» of the Medit. series (after Schmidt) but in the meantime it shows infiltrations of species belonging to the «Q. pubescens Gürtel» and to the «Quercus-Tilia-Acer Gürtel» of the Eurosib. Boreoam. series. This floristic arrangement is in accordance with the climatic-phytogeographic characters of this zone, which is to be referred to the «middle sub-zone of Lauretum» (Pavari) and to the contact zone between the semi-arid and the sub-humid levels (Emberger), where the «pluviofactor» (P/T of Lang) is still below 50. We are here near the upper margin of the Q. Ilex level, where haevy infiltrations of the upper zones are to be found.
doi: 10.1080/11263505209436484